Relationship between economic and financial performance and ESG practices in brazilian companies - Leite, Maurício; Moura, Franciele de; Soschinski, Caroline Keidann; Zanella, Cleunice (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Objective: The objective of this study is to analyze the relationship between economic-financial performance and ESG practices in Brazilian companies listed on B3. Methodology: The study is descriptive research with a quantitative approach, conducted through documental procedures. Data were collected from companies listed on B3 between 2018 and 2022, and panel data regression was used for analysis. Results: The results indicate that Return on Assets (ROA), Return on Equity (ROE), and Indebtedness (DEB) did not show a statistically significant influence on ESG practices. In contrast, Company Size (S) positively influences ESG practices, and Liquidity (LIQ) negatively influences them, with both relationships being statistically significant. The control variable Covid (COVID) showed a negative influence, but without statistical significance. These findings highlight the complexity and contextual dependence of the relationship between corporate characteristics and the adoption of ESG practices. Contributions of the Study: The study contributes by demonstrating that traditional financial metrics (ROA and ROE) do not effectively predict investment in ESG practices in Brazilian companies. It reveals the complexity of corporate decision-making, where liquidity acts negatively and size positively. This suggests that ESG practices are influenced by multiple factors beyond immediate financial performance, demanding a more holistic approach to sustainability.